Shifts in Pattern of Specialization: Case Studies of India and China - Widodo, Tri (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2008)
This paper examines shifts in pattern of specialization of Chinaâs and Indiaâs exported groups of products defined in the three-digit Standard International Trade Classification (SITC) Revision 2. This paper applies Revealed Symmetric Comparative Advantages (RSCA) index and Spearmanâs rank correlation. Some conclusions are withdrawn. First, on average the comparative advantages of both China and India increase, except in the case of China for the period of 1998-2003. Second, Chinaâs pattern of comparative advantage changes more dynamically than that of India. Third, the Chinaâs and Indiaâs patterns of comparative advantage show different trends (divergent/more complementary).